Política externa brasileira para o meio ambiente no Governo Bolsonaro: do protagonismo internacional ao negacionismo ambiental - Sousa, Mikaela Carla Lobo De (Universidade Federal do Tocantins, 2023)
The environment is one of the most relevant issues in contemporary global politics. International negotiations in this regard intensified increasingly from the 1970s onwards, and Brazil had an effective participation throughout this process. This work analyzes the Brazilian Foreign Policy for the environment of the government of Jair Bolsonaro (2019-2022) in relation to the historical trajectory of Brazil's performance in the main international environmental negotiations. Brazil has occupied a leading position since the Stockholm Conference, in 1972, at the Rio de Janeiro Conference, in 1992, and during the negotiating process of the International Regime on Climate Change, currently represented by the 2015 Paris Agreement. Since the beginning of Jair Bolsonaro's government, Brazilian environmental policy has been characterized, domestically and internationally, by the denial that there is an environmental crisis in the country. In this context, the present work has the general objective of identifying elements of continuities and changes in Brazilian foreign policy for the environment during the Bolsonaro government, having as reference the positions taken internationally by the country since the Stockholm Conference until the year 2018. Thus, the work was structured in three chapters. The first will go through the historical trajectory of the PEB for the environment, thus identifying the main arguments and lines of action of the country in this area. The second chapter will address the Bolsonaro government's environmental policy at the domestic and international levels. The third and final chapter will discuss, through a comparative analysis, the main continuities and changes that characterize the PEB for the environment of the Bolsonaro government in relation to the historical trajectory studied.